A MEMS coupled resonator for frequency filtering in air. (December 2018) - Ilyas, Saad; Jaber, Nizar; Younis, Mohammad I.
Abstract: We present design, fabrication, and characterization of a mechanically coupled MEMS H resonator capable of performing simultaneous mechanical amplification and filtering in air. The device comprises of two doubly clamped polyimide microbeams joined through the middle by a coupling beam of the same size. The resonator is fabricated via a multi-layer surface micromachining process. A special fabrication process and device design is employed to enable operation in air and to achieve mechanical amplification of the output response. Moreover, mixed-frequency excitation is used to demonstrate a tunable wide band filter for low frequency applications. It is demonstrated that through the multi-source harmonic excitation and the operation in air, an improved band-pass filter with flat response and minimal ripples can be achieved.